2020
DOI: 10.1037/ccp0000474
|View full text |Cite
|
Sign up to set email alerts
|

Does the group in group psychotherapy matter? A meta-analysis of the intraclass correlation coefficient in group treatment research.

Abstract: Objective: Over the last 3 decades, group treatment researchers have become increasingly knowledgeable of the impact of within-group dependency on analyses of group treatment data and of mutual influence processes that occur within therapy groups. Despite these advancements, there remains a lack of consensus on the magnitude of mutual influence, or group effects, in group treatment research. As such, this study sought to estimate the size of group effects on members' posttreatment outcomes by meta-analyzing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
1
14
2
Order By: Relevance
“…Our results showed that group effects explained a significant proportion of posttest depressive symptom levels (16%) even after controlling for baseline symptoms. This group-level variation is higher than variation reported in previous adult treatment studies (6-7%) [5,6,19]. In other words, some groups appeared more successful than others at reducing existing depressive symptoms during receipt of the group intervention.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Our results showed that group effects explained a significant proportion of posttest depressive symptom levels (16%) even after controlling for baseline symptoms. This group-level variation is higher than variation reported in previous adult treatment studies (6-7%) [5,6,19]. In other words, some groups appeared more successful than others at reducing existing depressive symptoms during receipt of the group intervention.…”
Section: Discussioncontrasting
confidence: 63%
“…This group-level phenomenon is known as a "clustering effect" and can be estimated using the intra-class correlation (ICC), which represents the ratio of group-level variation to total variation in the outcome [4]. Previous studies in adults have demonstrated the existence of significant clustering effects (or ICC) in group-based interventions (e.g., 6-7% of variance [5,6]).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Kivlighan et al (2019) examined 169 effect sizes from 37 group treatment studies, stressed group therapy members mutually influence their group posttreatment outcomes (e.g., depression, etc. ), and found that group membership explains about 6% of variance [ICC(1) = 0.06; Cohen's d of about 0.47].…”
Section: The Effect Of Measurement Error On Icc(1) Estimationmentioning
confidence: 99%
“…The intraclass coefficient (1) 1 (ICC(1)) reflects the degree of resemblance of micro-level units (e.g., events) within macro-level units (e.g., individuals), and is calculated as between-variance (e.g., variance, existing between groups or individuals) divided by total-variance (e.g., the sum of between-variance and the variance existing within groups or individuals; e.g., Fisher, 1934;Shrout and Fleiss, 1979;Snijders and Bosker, 2012). It is often used to provide insights of the magnitude of variance on different levels to test and inform psychological theories (e.g., Bliese et al, 2002;Castro, 2002;Nook et al, 2018;Kivlighan et al, 2019;Podsakoff et al, 2019). For example, Podsakoff et al (2019) showed that many psychological constructs (e.g., personality, coping, or job characteristics) vary substantially within-person (at least 40%), even though they "have historically been treated as between-person phenomena" (Podsakoff et al, 2019, p. 737).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation